1989
DOI: 10.1037/h0089766
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial adjustment to illness and family environment in dialysis patients.

Abstract: This study was undertaken to evaluate the impact of dialysis for end-stage renal disease on the psychosocial status of patients and their families. Twenty-one dialysis patients were studied initially and seven to 14 months later with the Psychosocial Adjustment to Illness Scale (PAIS), the Physician's Assessment Form (PAF), and the Family Environment Scale (FES). The FES was also given to a member of each patient's family. Over seven to 14 months, scores on the PAIS improved while those on the PAF did not chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…This scale measures three dimensions of the family environment: relationship (3 scales), personal growth (5 scales), and systems maintenance (2 scales). It has been used in many studies (10). Five subscales were selected for analysis: cohesion, expressiveness, conflict, independence, and control.…”
Section: The Evaluation Programmentioning
confidence: 99%
“…This scale measures three dimensions of the family environment: relationship (3 scales), personal growth (5 scales), and systems maintenance (2 scales). It has been used in many studies (10). Five subscales were selected for analysis: cohesion, expressiveness, conflict, independence, and control.…”
Section: The Evaluation Programmentioning
confidence: 99%
“…Drawing on strategic techniques high-lighting the gains and losses of change, the therapist held a session with father, aunt, and patient. Using such techniques as “split messages” (18), the therapist’s role included acknowledging the dilemmas facing the family, emphasizing its difficulties with immigration authorities and the enormous costs of failing to comply with treatment. Experiencing the understanding of the therapist about all aspects of its dilemma, the family became more supportive while maintaining pressure on the Home Office, which led to mother’s eventual arrival and assumption of Fatima’s care.…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…Pediatric renal dialysis and transplantation units treat children whose ages range from 0–16, a significant percentage of patients falling into the 13–16 age range. The few studies that have analyzed the impact of the family on patients’ treatment behavior have used samples of adults (18, 32, 37) or younger children (17, 21, 33). Researchers, clinicians (2, 6, 7, 11, 12, 44), and self-help groups such as the British Kidney Patients’ Association (22), have indicated that adolescents are particularly vulnerable to psychological problems and are more likely to have difficulties in complying with treatment.…”
mentioning
confidence: 99%
“…The importance of the relational realm of the friendly and loving environment for patients emerges chiefly in research focused on the quality of life of sick people (Cupa, 2002;Morelon et al, 2005;Belasco et al, 2006;Draskic et al, 2011;Czyzewski et al, 2018;Schouten et al, 2020). Some works focusing on the relatives of patients with chronic kidney disease have also been published (Kaye et al, 1989;Devins et al, 1997;White and Grenyer, 1999;Gee et al, 2005;Belasco et al, 2006), and there has been a succession of further articles in recent years (Roques and Proia-Lelouey, 2015;Gilbertson et al, 2019;Jean-Dit-Pannel and Thomas, 2019 among others). These studies describe how the sick person not only finds support from their partner, contributing to their well-being, but also underline the draining effect this can have on that family member (Kaye et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Some works focusing on the relatives of patients with chronic kidney disease have also been published (Kaye et al, 1989;Devins et al, 1997;White and Grenyer, 1999;Gee et al, 2005;Belasco et al, 2006), and there has been a succession of further articles in recent years (Roques and Proia-Lelouey, 2015;Gilbertson et al, 2019;Jean-Dit-Pannel and Thomas, 2019 among others). These studies describe how the sick person not only finds support from their partner, contributing to their well-being, but also underline the draining effect this can have on that family member (Kaye et al, 1989). Conversely, some patients insist on the overbearing nature of the role their spouse takes in daily life and care, which can undermine the relationship within the couple (Devins et al, 1997).…”
Section: Introductionmentioning
confidence: 99%